Screen time among preschoolers: exploring individual, familial, and environmental factors - Sangha Lee; Donghee Kim; Yunmi Shin (Clinical and Experimental Pediatrics)
Screen-based activity refers to the use of screened devices, which are changing from stationary devices such as televisions and desktop computers to newer portable devices such as smartphones and electronic tablets. The exposure of younger children to all types of screened devices has increased. This review aimed to provide an overview of previous studies and identify the correlations associated with screen-based activities in preschoolers. We conducted a systematic literature review of databases including PubMed, Embase, and PsycInfo targeting quantitative studies published between 2010 and 2019. We then analyzed the associations between screen time and various individual, familial, and environmental factors in healthy children aged 0–6 years. We specifically included studies that provided a subgroup analysis for this age category to systematically identify the factors influencing screen time patterns among preschoolers. The search yielded 36 articles that met the inclusion criteria. We investigated age, sex, and social, family, and personal factors as well as media parenting. The results suggested that media parenting for screen-based activities was an important protective factor. Limited research has been conducted on preschoolers' screen-based activities with both stationary and portable screened devices. Most factors have been studied using stationary devices and are too infrequent for solid conclusions to be reached. Parental screen time and the setting of appropriate media limits were crucial protective factors against excessive media exposure. However, information about family and personal factors remain scarce, and further research is needed.